Optimizing strength and corrosion resistance of the metastable β-alloy Ti–35Nb–7Zr–5Ta alloy by equal-channel angular pressing - R. Silva; J. Silva; C.C. Viana; C.R.M. Afonso; P. Hammer; D.C.C. Magalhães; A.H. Plaine; C.A.D. Rovere (Journal of Materials Research and Technology)
Controlling the microstructure of the Ti–35Nb–7Zr–5Ta alloy is fundamental for enhancing its strength and corrosion resistance in biomedical applications. This study examines how microstructural evolution through equal-channel angular pressing (ECAP) at room temperature and 300 °C influences Young's modulus, hardness, and corrosion resistance. ECAP refines grain size and promotes nanocrystalline β-phase grains, α'' phase decomposition, and ω phase precipitation. Room temperature ECAP decreases Young's modulus by reducing the β-phase stability due to deformation, while 300 °C processing enhances hardness and Young's modulus due to finer microstructure and higher ω-phase fraction. Grain refinement accelerates passivation kinetics, enhancing corrosion resistance with a thicker and less defective passive film, especially at 300 °C, without significant changes in the elemental composition of the outer passive film.